The ‘Sea Power’ Concept and Spanish-American War 1898: Reflexion of Captain A.T. Mahan - Piatnychuk, Taras (Before the Battle, 2023)
The article discusses the problem of results of and lessons from the Spanish-American war of 1898 through the «sea power» concept. American captain Alfred Thayer Mahan, who was the author of this concept, believed that the guarantee of the power and prosperity of any great political power was a powerful navy. In this view, the United States, which Mahan also counted among the mightiest world powers, should build its navy more actively.Not only did the war with Spain confirm Mahan’s ideas, but also allowed him to expand his concept, leading to the publication of his book Lessons of the war with Spain and other articles. Although Mahan noticed the successful ending of the war on land and at sea, he also pointed out some serious miscalculations that should be corrected as soon as possible. In particular, the US government had to take care of improving its coastal fortifications. If Spain had chosen the tactics of raiding coastal cities, the US would have suffered colossal damage.Other issues postulated by Mahan included increasing the number of warships and army units. In his opinion, it was necessary to allocate additional funds for that purpose and launch a publicity campaign to win the people’s support.While analysing the composition of the US Navy, Captain Mahan recommended focusing on the construction of two types of warships: battleships, to play the main role in sea battles and cruisers that, stripped of armour, were to serve as support for the battleships. Mahan also argued that the construction of older types of ships, such as monitors, should be abandoned.